An exploratory examination of the willingness to adopt mobile banking services - Inoubli, Chiheb Eddine; Sallami, Mourad (Edelweiss Applied Science and Technology, 2024)
The significance of digital marketing or mobile marketing is growing steadily as a potent strategy in service marketing. In this article, our focus is on unraveling the factors that shape an individual’s inclination to engage with mobile banking. Drawing on the Technology Acceptance Model (TAM), we gathered 350 questionnaires from mobile banking service users in Tunisia. Our analysis reveals that perceived attitude, trust, and word-of-mouth play a constructive and notable role in influencing the intention to use mobile banking. Furthermore, perceived usefulness and ease of use exert an indirect impact on the intention to adopt mobile banking.